(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The problem of school bullying is relevant, so it often rises in the literature. The article deals with the problems and features of school bullying, namely in adolescence. The causes of aggression among adolescents are considered.The study of teenage bullying is described.The content of the paper describges outstanding characteristics of bullying objects, subjects and other participants. The proposes her classification of bullying-parties in organization.The theme of the social context generating persecution is problematized.The problem of bullying is investigated more deeply.The study was aimed at identifying the type of bullying and studying the features of bullying among adolescents. The study concluded that psychological bullying is more common than physical bullying in adolescence.